Bioenergetic Model of the Highly Exploited Shark Mustelus schmitti under a Global Warming Context - Molina, Juan Manuel (2023)
Bioenergetic models are tools that allow the evaluation of the effect of environmental variables on fish growth. Successful implementation of this approach has been achieved in a few elasmobranch species. Our objective was to develop a bioenergetic model for Mustelus schmitti. The model developed showed a good fit to the field data available and accurately described the growth of this species. The practical example developed in this study provides novel population estimates of prey consumption and daily ration for the species. Results also indicate that this species would be susceptible to the effects of climate change. In the simulated climate change scenarios, the energy budget of M. schmitti was significantly altered, with increased food consumption and impaired growth. While there exists a number of limitations for the model developed in this article, namely its limitation to immature individuals, and its restricted temperature model, it provides an important tool for the management of this and other shark populations under heavy exploitation.